The recalibration of the Russian military to a war of attrition - Gjerstad, Michael (Politica, 2023)
This article provides an overview of Russia’s military capabilities in light of the war in Ukraine and what adaptations the Russian military has made in connection with the mobilization on 21 September 2022. This is examined by highlighting the military theoretical assumptions regarding the conduct of operations prior to the invasion, and how the adjustment to a war of attrition breaks with these previous military theoretical assumptions. The main question examined in the article is what significance this adaptation of the Russian military has in relation to the future of Russian military power and its ambitions for a Russian-led international order.